Variation of the Nutrient Foramen of Fibula and its Clinical Significance - Khatiwada, Sushma; Adhikari, Budhi Nath (Journal of Nobel Medical College, 2020)
Background: The fibula is a long bone located at the lateral aspect of the leg. Its diaphysis is principally nourished by one or more nutrient arteries entering the shaft through an opening referred to as the nutrient foramen. The present findings on the morphometrics of the foramen may be helpful to forensic experts, radiologists and clinicians for diagnosis and management of various bony conditions. Materials and Methods: This was a descriptive cross sectional study conducted on fifty dry adult human fibulae collected at the Department of Anatomy, Chitwan Medical College from June to September 2020. Total fibular length along with the number and location of all nutrient foramina present were recorded. Foraminal index of the fibula was calculated as well. Results: The study revealed that the average length of Nepalese fibulae was 34.1 ± 1.9 cm. Eighty-eight percent fibula had a single nutrient foramen, 4 % had two and 8 % had none. The most common location was between the medial crest and posterior border (63%, in fibula with single foramen), followed by the medial crest (30%) and between the medial crest and interosseous border (7%). The average foraminal index was 44.01 ± 7.9 % with a range of 34.9 to 65.7 %. Conclusion: Single nutrient foramen located at the middle third on posterior aspect was the most common finding. Regional data on the number and location of the foramina would be useful to forensic experts and clinicians for various diagnostic and treatment purposes.